Određivanje optimalnog organizacijskog oblika poštanskih šaltera - Havoić, Štefica (Promet - Traffic&Transportation, 2012)
This paper deals with adequate organization of postal window services with basic reference to the working environment in individual units of postal services network. Based upon known standards and criteria for provision of quality services an example has been provided of making optimal the system of provision of postal services to the user at the windows on post offices. The method for the selection of the most adequate allocation of services to individual windows by application of the theory of services provision has been applied to the concrete situation of the services system involving three operating windows.